Intellectual property and digital fashion: NFTS and the protection of virtual creations (Revista de Ensino em Artes, Moda e Design, 2025)
This article investigates the intersection between intellectual property and digital fashion in the context of NFTs (non-fungible tokens), exploring how this blockchain-based technology ensures authenticity and exclusivity for virtual creations. Using a mixed-methods approach, combining a literature review and case study analysis, the study primarily focuses on the legal aspects of NFT implementation in digital fashion, discussing regulatory challenges and implications for intellectual property protection. Economic and technological dimensions are acknowledged only as complementary perspectives and remain as avenues for future research. The conclusion is that, although NFTs offer new possibilities for the authentication and appreciation of digital assets, regulatory challenges remain that must be overcome to ensure legal certainty and sustainability in the digital fashion market. The article contributes to both academic and practical debates, proposing pathways for consolidating a digital ecosystem that balances innovation, copyright protection, and transparency in transactions.
Keywords: NFTs; digital fashion; intellectual property; blockchain